Utilization of information technology-based sources and facilities among medical professionals in Malaysia / Nurul Azurah Mohd Roni ... [et al.] - Mohd Roni, Nurul Azurah; Wan Mat Alli, Hasliza Ali; Wan Mat Alli, Wan Emilin; Engku Chik, Engku Razifah; Ab Hamid, Siti Azrin (Universiti Teknologi MARA, Selangor, 2020)
Information technology (IT) is an integral element in the process of information-seeking behaviour to fulfil research and clinical information needs due to pervasive access to information sources as well as facilities provided by libraries. The study aims to determine the frequency and level of importance of IT-based sources and facilities used among medical professionals in Malaysia. A cross-sectional study involving surveys with self-administered questionnaires was conducted among 336 medical professionals in ten medical institutions with libraries in Malaysia from November 2016 until April 2017. The respondents comprised medical officers, medical lecturers and postgraduate medical students. Medical practitioners who are legitimately registered with the Malaysian Medical Council and under professional training in the university were also included. The respondents were excluded if they were public members, general practitioners and dental practitioners. Descriptive analysis was used to present the findings. The mean (standard deviation) age of the respondents was 36.42 (7.98) years with their ages ranging from 24 to 71 years old. The majority of the respondents were of Malay ethnicity (72.5%), female (61.3%) and had a bachelor's degree (52.4%). The majority of the respondents utilised search engines and open access electronic journals to search for information. In response to IT-based sources and facilities, most of the respondents place a high level of importance on search engines (69.5%), followed by open access electronic journals (62.2%), library-subscribed databases (55.2%) and library websites (36.0%). Medical professionals in Malaysia are found to be frequent users of search engines, open access electronic journals and library subscribed databases to search for information for their research and clinical work. The study also found that search engines and open access electronic journals were considered by medical professionals to be highly important sources for searching information, followed by library-subscribed databases and library websites. Recommendations are proposed to maintain effective access to health information.